Impact of admission serum glucose level on in-hospital outcomes following coronary artery bypass grafting surgery - Imran, Syed Ali (Pulsus Group Inc, 2010)
OBJECTIVE: The impact of admission serum glucose (SG) level on outcomes in coronary artery bypass grafting (CABG) surgery is unknown. The present study sought to determine whether elevated admission SG level is associated with adverse outcomes following CABG surgery. METHODS: Patients undergoing CABG surgery between January 2000 and December 2005 at a single centre were identified (n=2856). Admission SG levels of less than 9.2 mmol/L and 9.2 mmol/L or greater were chosen to divide patients into two groups based on the 75th percentile of SG distribution. A logistic regression model was generated to determine the impact of admission SG level on a composite outcome of any one or more of in-hospital mortality, stroke, perioperative myocardial infarction, sepsis, deep sternal wound infection, renal failure, requirement for postoperative inotropes and prolonged ventilation. RESULTS: In total, 76.3% of patients had an admission SG level of less than 9.2 mmol/L (group A) and 23.7% had an admission SG level of 9.2 mmol/L or greater (group B). Group B patients were more likely to be female, have diabetes, have preoperative renal failure, have an ejection fraction of less than 40%, experience myocardial infarction within 21 days before surgery, and have triple vessel or left main disease (P<0.05). Univariate analysis revealed no difference in in-hospital mortality between group A (2.2%) and group B (3.2%) (P=0.12); however, the composite outcome was more likely to occur in group B (40.8%) versus group A (27.9%) (P=0.0001). After multivariable adjustment, admission SG level of 9.2 mmol/L or greater remained an independent predictor of composite outcome (OR=1.3, 95% CI 1.0 to 1.7, P=0.02, receiver operating characteristic = 78%). CONCLUSION: Admission SG level of 9.2 mmol/L or greater is associated with significant morbidity in patients undergoing CABG surgery.